2023
DOI: 10.1186/s12889-023-15494-1
|View full text |Cite
|
Sign up to set email alerts
|

Women’s empowerment and nutritional status of children in the Gambia: further analysis of the 2020 Gambia demographic and health survey

Abstract: Empowering women and the promotion of children’s health are key components of the Sustainable Development Goals targeted for achievement by 2030. The survival of young children, which depends on their nutrition, is influenced by an interaction of factors at the household level. This study aims to investigate the association between women’s empowerment and undernutrition among children under age 5 using The Gambia Demographic Health Survey (GDHS) 2019–20.Children’s undernutrition was measured with two indicator… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Compared to women from households with the lowest wealth index, those from wealthy households had increased probabilities of seeking to give their children MDD. Other favorable research works from the Gambia [ 44 ], Burkina Faso [ 45 ], Rwanda [ 34 ], and Ethiopia [ 24 ]. The lack of resources in poor homes to offer a balanced diet for the family members may account for the link between a low wealth index and under adequate MDD in children.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to women from households with the lowest wealth index, those from wealthy households had increased probabilities of seeking to give their children MDD. Other favorable research works from the Gambia [ 44 ], Burkina Faso [ 45 ], Rwanda [ 34 ], and Ethiopia [ 24 ]. The lack of resources in poor homes to offer a balanced diet for the family members may account for the link between a low wealth index and under adequate MDD in children.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, education confiscation limits women’s access to information about sexual and reproductive health, social exclusion from peers and decreased social mobility, which is accentuated by economic vulnerability 20–23. In addition, as an essential component of women’s empowerment, the discontinuation of education has an effect on a variety of adverse health outcomes for both mothers and their children 24 25. Therefore, it is crucial to identify the factors that influence the continuation of post-nuptial education, particularly in countries with widespread poverty and low educational enrolment 26…”
Section: Introductionmentioning
confidence: 99%
“…Most children did not receive adequate nutrition in the form of vitamins, proteins, and minerals due to poor health care and parents' lack awareness 8 . So that stunting and underweight are the headache of The Gambian children with a prevalence of 18% and 12% respectively 9 , 10 . This finding is corroborated by the 2021 Global Nutrition Report, which noted that The Gambia has not made much progress in reducing non-communicable diseases linked to diet and under-five stunting 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Numerous researches have shown that sociodemographic factors and meal frequency are related. Low levels of parental education, mother's age 9 , 16 , 17 , mother's work 18 , children's age and birth order 16 , 17 , household wealth status 9 , 16 , family size 16 , and place of residence 17 were thus substantially linked to low levels of dietary diversity practices. Additionally, the minimal meal frequency was substantially correlated with the birth interval 18 , 19 , satisfactory media exposure 16 , 17 , mother's participation in decision-making 17 , and maternal antenatal (ANC) and postnatal (PNC) care follow ups 19 , 20 .…”
Section: Introductionmentioning
confidence: 99%